PENGEMBANGAN FLIPBOOK BERBASIS PROJECT BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS VII SMP ISLAM SIRAJUN JADID PONTIANAK - Lobertus Sivi; Sandie; Hartono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study is to see the feasibility of developing project-based learning-based flipbooks on mathematical problem-solving abilities seen from validity, practicality and effectiveness. The method used is Research and Development (R&D) with an ADDIE research design. This research was carried out at Sirajun Jadid Islamic Junior High School Pontianak with a trial subject of 30 grade VII students. From the validity results, it shows that the validity of the media reaches a percentage of 89.08% and the validation of the material is a percentage of 97.73 with the criterion of "very valid". The Flipbook developed is also practical to use with the percentage of teacher response questionnaires of 92% of the "very practical" criteria and student response questionnaires of 92.47% of the "very practical" criteria. The effectiveness is seen from the results of the posttest with ,... Students are complete and ... incomplete students get a percentage of .... criteria of "very effective". Based on these results, it is concluded that the developed flipbook is suitable for use in learning.